Веб-система для взаємодії волонтерів з мешканцями та місцевими органами самоврядування у кризовий період - Строкоус, А. Б. (ХНУРЕ, 2023)
The web system aims to facilitate the interaction between volunteers and mission authorities during crisis periods by providing an efficient platform. This platform enables volunteers to submit and track the status of tasks while allowing mission authorities to manage and distribute these tasks effectively. The object of the work is to identify positive and negative aspects that affect the effectiveness of using websites by people with disabilities. The purpose of the work is to research and analysis of site accessibility criteria for a special group of users, the formation of results and conclusions, and the basis of testing